2016
DOI: 10.1083/jcb.201606092
|View full text |Cite
|
Sign up to set email alerts
|

MOZART1 and γ-tubulin complex receptors are both required to turn γ-TuSC into an active microtubule nucleation template

Abstract: Cells use γ-tubulin complex to nucleate microtubules. The assembly of active microtubule nucleator is spatially and temporally regulated through the cell cycle. Lin et al. show that the protein Mzt1/MOZART1 and γ-tubulin complex receptors directly interact and act together to assemble the γ-tubulin small complex into an active microtubule nucleation template and that such interaction is conserved between Candida albicans and human cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(108 citation statements)
references
References 49 publications
5
101
2
Order By: Relevance
“…In Co-IP experiments, CnnT-N, CM1 and MusCM1 strongly associated with γ-Tub, whereas CnnT-N with the Δ1 mutation (CnnT-N Δ1 ) did not (Figure 4C). These results are consistent with previous findings that CM1 is essential for activating γ-TuRCs to nucleate MTs [20, 27, 28]. …”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…In Co-IP experiments, CnnT-N, CM1 and MusCM1 strongly associated with γ-Tub, whereas CnnT-N with the Δ1 mutation (CnnT-N Δ1 ) did not (Figure 4C). These results are consistent with previous findings that CM1 is essential for activating γ-TuRCs to nucleate MTs [20, 27, 28]. …”
Section: Resultssupporting
confidence: 94%
“…Our study revealed that CM1 in Cnn is essential for activating γ-TuRC to initiate MT nucleation. Consistently, CM1 of other Cnn orthologs were shown to activate γ-TuRCs [20, 27, 32]. …”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Various proteins such as pericentrin, NEDD1/GCP‐WD, and CDK5RAP2 have been implicated in the regulation of γTuRCs . In addition, recent studies revealed that MOZART1 (human mitotic‐spindle organizing protein associated with a ring of γ‐tubulin 1) protein may equally be involved in this regulation …”
Section: Introductionmentioning
confidence: 99%